2022
DOI: 10.1186/s13195-022-01095-4
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable and non-modifiable risk factors of dementia on midlife cerebral small vessel disease in cognitively healthy middle-aged adults: the PREVENT-Dementia study

Abstract: Background Considerable overlap exists between the risk factors of dementia and cerebral small vessel disease (SVD). However, studies remain limited to older cohorts wherein pathologies of both dementia (e.g. amyloid) and SVD (e.g. white matter hyperintensities) already co-exist. In younger asymptomatic adults, we investigated differential associations and interactions of modifiable and non-modifiable inherited risk factors of (future) late-life dementia to (present-day) mid-life SVD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“… 51 WMH volume did not differ by APOEɛ4 status or family history of dementia in unadjusted analysis or adjusted analyses controlling for sex, age, education and site. 18 WMH burden increased with older age in both the unadjusted ( t = 8.15, P < 0.001) and adjusted analysis controlling for sex, education and site ( t = 7.91, P < 0.001). Males (2.99 ml) had greater WMH volumes than females (1.81 ml), even after normalizing for head size [(WMH volume/intracranial volume) ∗ 100%; males = 0.16, females = 0.11]—results were significant in both unadjusted ( ρ = 0.25, P < 0.001) and covariate-adjusted analyses of WMH burden ( t = 5.41, P < 0.001).…”
Section: Results: Description Of Prevent V7000 Data Setmentioning
confidence: 96%
“… 51 WMH volume did not differ by APOEɛ4 status or family history of dementia in unadjusted analysis or adjusted analyses controlling for sex, age, education and site. 18 WMH burden increased with older age in both the unadjusted ( t = 8.15, P < 0.001) and adjusted analysis controlling for sex, education and site ( t = 7.91, P < 0.001). Males (2.99 ml) had greater WMH volumes than females (1.81 ml), even after normalizing for head size [(WMH volume/intracranial volume) ∗ 100%; males = 0.16, females = 0.11]—results were significant in both unadjusted ( ρ = 0.25, P < 0.001) and covariate-adjusted analyses of WMH burden ( t = 5.41, P < 0.001).…”
Section: Results: Description Of Prevent V7000 Data Setmentioning
confidence: 96%
“…There is no causal genetic relationship between the two, which aligns with the results of the present study. In addition, vascular dementia is the second most common type of dementia after Alzheimer's disease [6,30] . Hearing impairment as a risk factor is associated with vascular dementia, which may be related to in ammatory responses, oxidative stress in cells, or even the pathogenesis of blood circulation disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, at this early stage whereby all participants in the study are cognitively asymptomatic, we have shown that the dominant risk gene for sporadic AD modulates differentially the association between cerebral perfusion and RDW, mainly in distal vascular territories. Further investigation is thus warranted on how hemodynamic and potentially hemorheological properties could be interacting with APOE4 carriership in impacting cerebrovascular health and physiology, especially in the absence of prominent differences both physiologically and structurally 73 , 74 between APOE4 carriers and non-carriers.…”
Section: Discussionmentioning
confidence: 99%